The Role of Industries in Rising Inequality - Juraj Briskar; Edoardo di Porto; José V. Rodriguez Mora; Cristina Tealdi (Institute of Labor Economics (IZA), 2023)
We analyse thirty years of Italian private sector employment data (1985-2018) to study the dynamics of rising earnings inequality. The total variance surged by 10 log points, with 55% occurring between industries, particularly in a few low-paid service sectors. Workers with low earnings ability showed increased likelihood of working in industries with low average firm premium (sorting) together with other low-earning workers (segregation). Strikingly, parallels with the US emerge. In both, inequality increased predominantly between industries and concentrated within a small number of sectors. Italy's increase primarily stems from low-paying sectors, diverging from the more balanced growth observed in the US across high-paying and low-paying industries. Our findings suggest that despite institutional differences similar underlying forces are at work.
Keywords: E02; E25; J01; 330; earnings inequality; industries; sorting; segregation